Influence of Curing Humidity on the Compressive Strength of Gypsum-Cemented Similar Materials - Weiming Guan; Dongsheng Zhang; Yingyuan Wen; Xufeng Wang (Advances in Materials Science and Engineering)
The analogous simulation experiment is widely used in geotechnical and mining engineering. However, systematic errors derived from unified standard curing procedure have been underestimated to some extent. In this study, 140 gypsum-cemented similar material specimens were chosen to study their curing procedure with different relative humidity, which is 10%–15%, 40%, 60%, and 80%, respectively. SEM microstructures and XRD spectra were adopted to detect the correlation between microstructures and macroscopic mechanical strength during curing. Our results indicated that the needle-like phases of similar materials began to develop in the early stage of the hydration process through intersecting with each other and eventually transformed into mat-like phases. Increase of humidity may inhibit the development of needle-like phases; thus the compressive strength changes more smoothly, and the time required for the material strength to reach the peak value will be prolonged. The peak strength decreases along with the increase of humidity while the humidity is higher than 40%; however, the reverse tendency was observed if the humidity was lower than 40%. Finally, we noticed that the material strength usually reaches the peak value when the water content continuously reduces and tends towards stability. Based on the above observation, a curing method determination model and experimental strength predication method for gypsum-cemented similar materials were proposed.